Dehumidifier Box Installation in Electro-Hydraulic Control Oil Tank System to Improve Asset Reliability Program - Ruswandi, Isya Agung; Niman, Dede; Anggriawan, Egi (Journal of Mechanical Design and Testing, 2025)
Phosphate ester is a synthetic lubricant with the advantage of being a fluid that has excellent heat resistance/ fire-resistant fluid. Therefore, phosphate ester oil is widely used in EHC (Electro-Hydraulic Control) systems to regulate the opening of high-temperature steam valves, such as those used in Control Oil Steam 4.3 at PT PLN Indonesia Power Priok Block 4. Despite its advantages, phosphate ester oil has a natural hygroscopic property that allows it to absorb water from the atmosphere. This can initiate the hydrolysis process, which can lead to oil deterioration. In this study, the behavior of the water absorption rate by phosphate ester was observed under ambient humidity conditions from year 2020 to 2023. Subsequently, an innovative dehumidifier box was designed based on the idea of controlling humidity around the control oil tank and was implemented in October 2023. Observations were conducted again for nine months to monitor the behavior of the water absorption rate by phosphate ester under controlled humidity conditions. The results of the observation of the water absorption rate by phosphate ester under ambient humidity (50- 80%) showed a high increase of 24 to 62 ppm per month, causing the water content to exceed the warning limit (max. 1000 ppm), necessitating high maintenance costs ranging from Rp 37,830,000 to Rp 363,584,000 or more annually to maintain the quality of the lubricant. In contrast, the results of the observation of the water absorption rate under controlled humidity conditions (20%) showed a much lower rate of 19 ppm per month, not exceeding the warning limit. Based on these findings, it can be concluded that humidity control using the innovative dehumidifier box significantly reduces the water absorption rate by phosphate ester oil, thereby minimizing oil deterioration and saving maintenance costs.